Rewarding value‐creating ideas in organizations: The power of low‐powered incentives. (29th April 2013) - Baumann, Oliver; Stieglitz, Nils
<x xml:space="preserve">Abstract</x> Ideas from employees are a major source of value creation in firms, yet the merits of rewards for incentivizing the generation of ideas are highly contested. Using a computational model, we show that firms can improve performance by offering low‐powered rewards for the selection and implementation of employee ideas. Low‐powered incentives provide a sufficient stream of good ideas, but few exceptional ones. Higher‐powered incentives, in contrast, do not systematically translate into exceptional ideas either, but generate an excessive number of good ideas. Performance‐based rewards thus appear to be a blunt tool to harness the long tail of innovation. We develop propositions to guide empirical research and discuss their implications for strategy and organizational design. Copyright © 2013 John Wiley & Sons, Ltd.